Analysis of Claims for Material and Non-Material Damages for Damaged Goods in Transit Against a Freight Company and the Forgery of Insurance Payment Evidence - Adi Nugroho Kuspratama; Ratna Dewi; Irawati Irawati; Jujun Wardoyo; Sara Irianti (CV. Publikasi Indonesia, 2026)
This research aims to analyze legal aspects related to material and immaterial compensation lawsuits for damage to goods in the delivery process by cargo companies and the falsification of insurance payment receipts. This problem is important because it concerns legal protection for consumers and the responsibility of business actors in goods transportation activities. The research method used is quantitative with a legislative approach and a conceptual approach, supported by a literature study of various primary and secondary legal sources. The results of the study show that cargo companies are in principle responsible for damage to goods that occur during the delivery process, unless it can be proven that there are compelling circumstances. However, in the case of falsification of proof of insurance payment, there is an element of unlawful acts that strengthen the basis of a lawsuit for the aggrieved party. Material damages can be sued based on actual losses suffered, while immaterial damages relate to non-economic losses such as inconvenience and psychological losses. In addition, such acts of counterfeiting have the potential to have criminal legal consequences that have an impact on civil liability. In conclusion, legal protection for shipping service users needs to be strengthened through the enforcement of cargo company liability and supervision of insurance practices in the transportation of goods. This research is expected to contribute to the development of civil law, especially in the aspects of consumer accountability and protection